Dampak Peralihan Hak Asuh Anak yang Belum Mumayyiz Menurut Hukum Islam - Dewi Sartika (Peduli Riset dan Pengabdian Masyarakat, 2024)
Basically, mothers have more rights than fathers in terms of child care, however, when there is a divorce case, there are many cases of child custody disputes in the Religious Courts in Indonesia, many of which are still found that the mother is disqualified as the holder of the child's rights who have not yet mumayyiz because there are provisions that are not met. This study aims to determine the rights of child custody according to Islamic Law, the transfer of child custody rights that have not yet mumayyiz due to the loss of the mother as the holder of child custody rights and its impact on the status of the child according to Islamic Law and a comparison of the transfer of child custody rights that have not yet mumayyiz due to the loss of the mother as the holder of child custody rights according to Islamic Law and Positive Law in Indonesia. This study is a library research by collecting data from the Qur'an, Hadith, Compilation of Islamic Law, Legislation, Civil Law and Child Protection Law relating to the impact of the transfer of child custody rights that have not yet mumayyiz and secondary data sources, namely previous research, journals, articles that are relevant to the theme of this study. The author uses descriptive data analysis, namely describing, presenting or explaining various existing data/theories related to the impact of the transfer of child custody rights that are not yet mumayyiz according to Islamic Law. The results of the study explain that according to Islamic Law, child custody (hadhanah) is the maintenance of children who are not yet independent or who are not yet mumayyiz and who still need education, care or supervision and affection from their parents so as not to endanger their lives or bodies. The transfer of child custody rights that are not yet mumayiz due to the mother's demise as the holder of child custody rights is caused by the mother's physical and mental inability, the mother's immoral behavior, and others. The impact of the transfer of child custody rights that are not yet mumayyiz due to the demise of the mother as the holder of child custody rights for the child's status according to Islamic Law is in several ways, namely legal status: custody rights: lineage rights (descent) and maintenance rights. The comparison of the transfer of custody of children who have not yet mumayyiz due to the death of the mother as the holder of child custody according to Islamic Law and Positive Law in Indonesia is that it has similarities in giving custody rights to the mother for children who have not yet mumayyiz, with the possibility of transferring custody rights to the father if the mother dies and in the principle of the best interests of the child.